"Losing language is a loss of nation": transnational movement to preserve Mon scripts in Thailand. - Chaisingkananont, Somrak; Pasitpakakul, Pattama (Inter-Asia Cultural Studies, 2024)
Nowadays, over one million Mon-speaking people live in Mon communities of southeastern Myanmar, and the Mon descendants live in Thailand and across various nations. This paper examines the transnational movements among the Mons in Thailand, the oversea Mons and the Mon migrants from Myanmar to preserve Mon written language. Based on documentary research and multi-sited ethnographic research in Thailand, this study has found that Theravada Buddhist monks who can read and write the Mon scripts play a major role as mediators between Mon communities in several countries and thus led to the establishment of a transnational Mon ethnic network. With the fear that the loss of the Mon language will inevitably result in the loss of Mon culture, there have been ethno-nationalist movements to preserve the precious Mon manuscripts and provide alternative forms of Mon language education to the Myanmar-Mon youth and migrants' children in the Buddhist Monasteries of Thailand. Mon elites strive for Mon language transmission to the youth and children as well as taking steps to invent the fonts of Mon scripts and new applications to use Mon language in the new media. The findings shed light on their ongoing attempts to preserve the vitality of their languages in a variety of media and to transmit Mon-ness in the changing context of globalization.